Leveraging Artificial Intelligence for Seamless Data Access in Big Data Ecosystems - Martin, Sophie; Dupont, Lucas (MZ Journal of Artificial Intelligence, 2024)
Big Data ecosystems have become a cornerstone for businesses and research, enabling the analysis of massive and complex datasets to derive valuable insights. However, the sheer volume, variety, and velocity of Big Data pose significant challenges in terms of data access, retrieval, and management. Artificial Intelligence (AI) offers innovative solutions to these challenges by automating data discovery, enhancing data retrieval, and optimizing data management processes. This paper explores how AI can be leveraged to enable seamless data access in Big Data ecosystems. It discusses the application of AI-driven techniques such as natural language processing (NLP) for intuitive data querying, machine learning for data indexing and retrieval, and AI-powered data governance for improved data quality and accessibility.